2018
DOI: 10.1111/jvp.12709
|View full text |Cite
|
Sign up to set email alerts
|

Application of different pharmacokinetic models to describe and predict pharmacokinetics of voriconazole in magellanic penguins following oral administration

Abstract: Aspergillosis is a condition causing serious morbidity and mortality in captive penguins and other bird species. It can be treated with antifungal drugs, such as voriconazole. However, the pharmacokinetics of voriconazole are variable between different animal and bird species. Therefore, the pharmacokinetics of voriconazole were investigated in this study in Magellanic penguins. Pharmacokinetic models were constructed and applied to predict the pharmacokinetics of voriconazole during long-term treatment in Mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The possibility of different genes in these two species of penguin is supported by findings by Almeida et al An evolutionary phylogeny of the loss/gain of CYP2 subfamilies shows that the CYP2C subfamily has been lost in the Adelie penguin species but has remained in the emperor penguin . In agreement with Parsley et al, given the differences identified between Adelie and emperor penguin species, the possibility that Magellanic penguins lack or express specific CYP enzymes to a different extent should not be excluded. The results presented here may suggest that the CYP2C subfamily has been lost or has reduced expression in the Magellanic penguins but has remained in the African penguins.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The possibility of different genes in these two species of penguin is supported by findings by Almeida et al An evolutionary phylogeny of the loss/gain of CYP2 subfamilies shows that the CYP2C subfamily has been lost in the Adelie penguin species but has remained in the emperor penguin . In agreement with Parsley et al, given the differences identified between Adelie and emperor penguin species, the possibility that Magellanic penguins lack or express specific CYP enzymes to a different extent should not be excluded. The results presented here may suggest that the CYP2C subfamily has been lost or has reduced expression in the Magellanic penguins but has remained in the African penguins.…”
Section: Discussionmentioning
confidence: 88%
“…When drugs are given orally to birds, they can be given as the tablet or capsule directly into the esophagus of the bird or, more commonly, can be included in a solution formulation that the bird either drinks or is given in a syringe. For fisheating birds such as penguins, it is also common that a drug suspension is incorporated into a fish (e.g., herring) that is then fed to the bird (e.g., Parsley et al 43 ). When a liquid is prepared extemporaneously for a bird, it is often mixed with water and a commercial suspending agent to make a suspension.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations